ANALYZING THE EFFECT OF MICROPLASTIC PARTICLES ON HUMAN PODOCYTES - Yarbakht, Melina; Sarau, George; Kling, Lasse; Müller-Deile, Janina; Kotb, Ahmed; Christiansen, Silke; Schiffer, Mario (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2021)
CRIS-Team WoS Importer:2021-12-03

A new rescue regimen with plasma exchange and rituximab in high-risk membranous glomerulonephritis - Müller-Deile, Janina; Schiffer, Lena; Hiss, Marcus; Haller, Hermann; Schiffer, Mario (European Journal of Clinical Investigation, 2015)
BACKGROUND: Even though current treatment guidelines for idiopathic membranous glomerulonephritis (iMGN) exist, many questions regarding an optimal therapy remain unanswered. Complete remission cannot be achieved in all patients; relapses occur, in some cases frequently, and side effects from the immunosuppressive therapy are common. Therapeutic options in high-risk patients not responding to standard immunosuppressive therapies are limited. Recent research reveals that the human M-type phospholipase A2 receptor (PLA2 R) is a causative factor in iMGN that parallels clinical disease activity. However, in some patients, this correlation is not evident and additional undetermined factors seem to play a role. DESIGN: We evaluated a new rescue protocol including plasma exchanges (PE) against albumin, intravenous immunoglobulins (IVIGs) and rituximab for 10 patients with a biopsy-proven diagnosis of iMGN who were therapy-resistant to all conventional regimens and had a urinary protein to creatinine ratio of more than 10 000 mg/g Crea. We compared this protocol with standard immunosuppressive protocols including monthly alternating prednisolone plus cyclophosphamide (18 patients), cyclosporine plus prednisolone (23 patients) and rituximab alone (eight patients) in a retrospective design. RESULTS: Our rescue regimen with PE, IVIGs and rituximab achieved partial remission in 90% of patients who had been otherwise refractory to therapy. The mean time to partial remission was 2·1 months. Furthermore, two anti-PLA2 R-antibody negative patients were also treated with this rescue regimen, achieving partial remission after 1 and 4 months. CONCLUSION: A combination of PE, IVIGs and rituximab is a treatment option to consider for high-risk patients with iMGN who are refractory to conventional therapy.
EVALuna2:34561

Antiphospholipase A2 receptor autoantibodies: A comparison of three different immunoassays for the diagnosis of idiopathic membranous nephropathy - Behnert, Astrid; Schiffer, Mario; Müller-Deile, Janina; Beck, Laurence H.; Mahler, Michael; Fritzler, Marvin J. (Journal of Immunology Research, 2014)
Background. The recent identification of circulating autoantibodies directed towards the M-type phospholipase A2 receptor (PLA 2R) has been a major advancement in the serological diagnosis of idiopathic membranous nephropathy (IMN), a common cause of nephrotic syndrome in adults. The goal of this study was to compare the performance characteristics of two commercial assays as well as the first addressable laser bead immunoassay (ALBIA) developed for the detection of anti-PLA2R antibodies. Methods. Serum samples of 157 IMN patients and 142 controls were studied. Samples were tested by a cell based immunofluorescence assay (CBA-IFA, Euroimmun, Germany), by ELISA (Euroimmun), and by a novel ALBIA employing an in vivo expressed recombinant human PLA2R. Results. Overall, the three assays showed significant qualitative and quantitative correlation. As revealed by receiver operating characteristic analysis, the ALBIA correlated better with the CBA-IFA than the ELISA (P = 0.0003). The clinical sensitivities/ specificities for IMN were 60.0% (51.0-68.5%)/98.6% (95.0-99.8%) and 56.2% (47.2-64.8%)/100.0% (97.4-100.0%) for ALBIA and CBA-IFA, respectively. Conclusion. The ALBIA represents a promising assay for the detection of anti-PLA2R antibodies showing similar performance to the CBA-IFA and the advantage of ease of use and suitability for high throughput, rapid turnaround times, and multiplexing. © 2014 Astrid Behnert et al.
CRIS-Team Scopus Importer:2020-11-12

A Tight Control of Non-Canonical TGF-β Pathways and MicroRNAs Downregulates Nephronectin in Podocytes - Sopel, Nina; Ohs, Alexandra; Schiffer, Mario; Müller-Deile, Janina (Cells, 2022)
Nephronectin (NPNT) is an extracellular matrix protein in the glomerular basement membrane that is produced by podocytes and is important for the integrity of the glomerular filtration barrier. Upregulated transforming growth factor β (TGF-β) and altered NPNT are seen in different glomerular diseases. TGF-β downregulates NPNT and upregulates NPNT-targeting microRNAs (miRs). However, the pathways involved were previously unknown. By using selective inhibitors of the canonical, SMAD-dependent, and non-canonical TGF-β pathways, we investigated NPNT transcription, translation, secretion, and regulation through miRs in podocytes. TGF-β decreased NPNT mRNA and protein in cultured human podocytes. TGF-β-dependent regulation of NPNT was meditated through intracellular signaling pathways. Under baseline conditions, non-canonical pathways predominantly regulated NPNT post-transcriptionally. Podocyte NPNT secretion, however, was not dependent on canonical or non-canonical TGF-β pathways. The canonical TGF-β pathway was also dispensable for NPNT regulation after TGF-β stimulation, as TGF-β was still able to downregulate NPNT in the presence of SMAD inhibitors. In contrast, in the presence of different non-canonical pathway inhibitors, TGF-β stimulation did not further decrease NPNT expression. Moreover, distinct non-canonical TGF-β pathways mediated TGF-β-induced upregulation of NPNT-targeting miR-378a-3p. Thus, we conclude that post-transcriptional fine-tuning of NPNT expression in podocytes is mediated predominantly through non-canonical TGF-β pathways.
CRIS-Team Scopus Importer:2022-01-21
Keywords: MicroRNAs; Nephronectin; Podocytes; Podocytopathies; Post-transcriptional regulation; TGF-β

Author Correction: Novel diagnostic and therapeutic techniques reveal changed metabolic profiles in recurrent focal segmental glomerulosclerosis (Scientific Reports, (2021), 11, 1, (4577), 10.1038/s41598-021-83883-w) - Müller-Deile, Janina; Sarau, George; Kotb, Ahmed M.; Jaremenko, Christian; Rolle-Kampczyk, Ulrike E.; Daniel, Christoph; Kalkhof, Stefan; Christiansen, Silke H.; Schiffer, Mario (Scientific Reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.
CRIS-Team Scopus Importer:2021-06-04

Can Gene Expression Analysis in Zero-Time Biopsies Predict Kidney Transplant Rejection? - Vonbrunn, Eva; Angeloni, Miriam; Büttner-Herold, Maike; Müller-Deile, Janina; Heller, Katharina M.; Bleich, Erik; Söllner, Stefan; Amann, Kerstin Ute; Ferrazzi, Fulvia; Daniel, Christoph (Frontiers in Medicine, 2022)
Zero-time biopsies are taken to determine the quality of the donor organ at the time of transplantation. Histological analyses alone have so far not been able to identify parameters that allow the prediction of subsequent rejection episodes or graft survival. This study investigated whether gene expression analyses of zero-time biopsies might support this prediction. Using a well-characterized cohort of 26 zero-time biopsies from renal transplant patients that include 4 living donor (LD) and 22 deceased donor (DD) biopsies that later developed no rejection (Ctrl, n = 7), delayed graft function (DGF, n = 4), cellular (T-cell mediated rejection; TCMR, n = 8), or antibody-mediated rejection (ABMR, n = 7), we analyzed gene expression profiles for different types of subsequent renal transplant complication. To this end, RNA was isolated from formalin-fixed, paraffin-embedded (FFPE) sections and gene expression profiles were quantified. Results were correlated with transplant data and B-cell, and plasma cell infiltration was assessed by immunofluorescence microscopy. Both principal component analysis and clustering analysis of gene expression data revealed marked separation between LDs and DDs. Differential expression analysis identified 185 significant differentially expressed genes (adjusted p < 0.05). The expression of 68% of these genes significantly correlated with cold ischemia time (CIT). Furthermore, immunoglobulins were differentially expressed in zero-time biopsies from transplants later developing rejection (TCMR + ABMR) compared to non-rejected (Ctrl + DGF) transplants. In addition, immunoglobulin expression did not correlate with CIT but was increased in transplants with previous acute renal failure (ARF). In conclusion, gene expression profiles in zero-time biopsies derived from LDs are markedly different from those of DDs. Pre-transplant ARF increased immunoglobulin expression, which might be involved in triggering later rejection events. However, these findings must be confirmed in larger cohorts and the role of early immunoglobulin upregulation in zero-biopsies needs further clarification.
CRIS-Team Scopus Importer:2022-04-29
Keywords: inflammation; kidney transplantation; mRNA expression; outcome; zero-time biopsy

Characterizing Intraindividual Podocyte Morphology In Vitro with Different Innovative Microscopic and Spectroscopic Techniques - Kraus, Annalena; Rose, Victoria; Krüger, René; Sarau, George; Kling, Lasse; Schiffer, Mario; Christiansen, Silke; Müller-Deile, Janina (Cells, 2023)
Podocytes are critical components of the glomerular filtration barrier, sitting on the outside of the glomerular basement membrane. Primary and secondary foot processes are characteristic for podocytes, but cell processes that develop in culture were not studied much in the past. Moreover, protocols for diverse visualization methods mostly can only be used for one technique, due to differences in fixation, drying and handling. However, we detected by single-cell RNA sequencing (scRNAseq) analysis that cells reveal high variability in genes involved in cell type-specific morphology, even within one cell culture dish, highlighting the need for a compatible protocol that allows measuring the same cell with different methods. Here, we developed a new serial and correlative approach by using a combination of a wide variety of microscopic and spectroscopic techniques in the same cell for a better understanding of podocyte morphology. In detail, the protocol allowed for the sequential analysis of identical cells with light microscopy (LM), Raman spectroscopy, scanning electron microscopy (SEM) and atomic force microscopy (AFM). Skipping the fixation and drying process, the protocol was also compatible with scanning ion-conductance microscopy (SICM), allowing the determination of podocyte surface topography of nanometer-range in living cells. With the help of nanoGPS Oxyo®, tracking concordant regions of interest of untreated podocytes and podocytes stressed with TGF-β were analyzed with LM, SEM, Raman spectroscopy, AFM and SICM, and revealed significant morphological alterations, including retraction of podocyte process, changes in cell surface morphology and loss of cell-cell contacts, as well as variations in lipid and protein content in TGF-β treated cells. The combination of these consecutive techniques on the same cells provides a comprehensive understanding of podocyte morphology. Additionally, the results can also be used to train automated intelligence networks to predict various outcomes related to podocyte injury in the future.
CRIS-Team Scopus Importer:2023-05-26
Keywords: atomic force microscopy; filopodia; foot processes; light microscopy; nanoGPS tracking; podocytes; Raman spectroscopy; scanning electron microscopy; scanning ion-conductance microscopy; single-cell RNA sequencing

Chemokine/Cytokine Levels Correlate with Organ Involvement in PR3-ANCA-Associated Vasculitis - Müller-Deile, Janina; Jaremenko, Christian; Haller, Hermann; Schiffer, Mario; Haubitz, Marion; Christiansen, Silke; Falk, Christine; Schiffer, Lena (Journal of Clinical Medicine, 2021)
Background: ANCA-associated vasculitis (AAV) is a rare small vessel disease characterized by multi-organ involvement. Biomarkers that can measure specific organ involvement are missing. Here, we ask whether certain circulating cytokines and chemokines correlate with renal involvement and if distinct cytokine/chemokine patterns can differentiate between renal, ear/nose/throat, joints, and lung involvement of AAV. Methods: Thirty-two sets of Birmingham vasculitis activity score (BVAS), PR3-ANCA titers, laboratory marker, and different cytokines were obtained from 17 different patients with AAV. BVAS, PR3-ANCA titers, laboratory marker, and cytokine concentrations were correlated to different organ involvements in active AAV. Results: Among patients with active PR3-AAV (BVAS > 0) and kidney involvement we found significant higher concentrations of chemokine ligand (CCL)-1, interleukin (IL)-6, IL21, IL23, IL-28A, IL33, monocyte chemoattractant protein 2 (MCP2), stem cell factor (SCF), thymic stromal lymphopoietin (TSLP), and thrombopoietin (TPO) compared to patients without PR3-ANCA-associated glomerulonephritis. Patients with ear, nose, and throat involvement expressed higher concentrations of MCP2 and of the (C-X-C motif) ligand-12 (CXCL-12) compared to patients with active AAV and no involvement of these organs. Conclusion: We identified distinct cytokine patterns for renal manifestation and for ear, nose and throat involvement of PR3-AAV. Distinct plasma cytokines might be used as non-invasive biomarkers of organ involvement in AAV.
CRIS-Team WoS Importer:2021-07-09

CIN85 Deficiency Prevents Nephrin Endocytosis and Proteinuria in Diabetes - Teng, Beina; Schroder, Patricia; Müller-Deile, Janina; Schenk, Heiko; Staggs, Lynne; Tossidou, Irini; Dikic, Ivan; Haller, Hermann; Schiffer, Mario (Diabetes, 2016)
Diabetic nephropathy (DN) is the major cause of end-stage renal disease worldwide. Podocytes are important for glomerular filtration barrier function and maintenance of size selectivity in protein filtration in the kidney. Podocyte damage is the basis of many glomerular diseases characterized by loss of interdigitating foot processes and decreased expression of components of the slit diaphragm. Nephrin, a podocyte-specific protein, is the main component of the slit diaphragm. Loss of nephrin is observed in human and rodent models of diabetic kidney disease. The long isoform of CIN85 (RukL) is a binding partner of nephrin that mediates nephrin endocytosis via ubiquitination in podocytes. Here we demonstrate that the loss of nephrin expression and the onset of proteinuria in diabetic mice correlate with an increased accumulation of ubiquitinated proteins and expression of CIN85/RukL in podocytes. CIN85/RukL deficiency preserved nephrin surface expression on the slit diaphragm and reduced proteinuria in diabetic mice, whereas overexpression of CIN85 in zebrafish induced severe edema and disruption of the filtration barrier. Thus, CIN85/RukL is involved in endocytosis of nephrin in podocytes under diabetic conditions, causing podocyte depletion and promoting proteinuria. CIN85/RukL expression therefore shows potential to be a novel target for antiproteinuric therapy in diabetes.
EVALuna2:34554

Disease modeling in genetic kidney diseases: zebrafish - Schenk, Heiko; Müller-Deile, Janina; Kinast, Mark; Schiffer, Mario (Cell and Tissue Research, 2017)
Growing numbers of translational genomics studies are based on the highly efficient and versatile zebrafish (Danio rerio) vertebrate model. The increasing types of zebrafish models have improved our understanding of inherited kidney diseases, since they not only display pathophysiological changes but also give us the opportunity to develop and test novel treatment options in a high-throughput manner. New paradigms in inherited kidney diseases have been developed on the basis of the distinct genome conservation of approximately 70 % between zebrafish and humans in terms of existing gene orthologs. Several options are available to determine the functional role of a specific gene or gene sets. Permanent genome editing can be induced via complete gene knockout by using the CRISPR/Cas-system, among others, or via transient modification by using various morpholino techniques. Cross-species rescues succeeding knockdown techniques are employed to determine the functional significance of a target gene or a specific mutation. This article summarizes the current techniques and discusses their perspectives.
EVALuna2:34551

Distinct Changes in Gut Microbiota of Patients with Kidney Graft Rejection - Visconti, Vanessa; Wirtz, Stefan; Schiffer, Mario; Müller-Deile, Janina (Transplantation Direct, 2024)
Background. Kidney graft rejection still represents the major cause of graft loss in kidney transplant recipients. Of growing interest is the bidirectional relationship between gut microbiome and immune system suggesting that gut microbiota can affect allograft outcome. Methods. In this cross-sectional case-control study, we characterized the gut microbial profile of adult renal transplant recipients with and without graft rejection to define a cohort-specific microbial fingerprint through 16S ribosomal RNA gene sequencing. We used very strict inclusion and exclusion criteria to address confounder of microbiota composition. Results. Different relative abundances in several gut microbial taxa were detectable in control patients compared with patients with kidney allograft rejection. Alpha diversity was lower in the rejection group and beta diversity revealed dissimilarity between patients with and without kidney graft rejection (P < 0.01). When the rejection group was stratified according to different types of allograft rejection, major changes were identified between patients with chronic T-cellular-mediated rejection and controls. Changes in alpha diversity within the gut microbiome were related to the probability of chronic T-cellular-mediated rejection (P < 0.05). Kidney transplant patients without rejection showed significant enrichment of rather anti-inflammatory taxa whereas in the rejection group bacteria well known for their role in chronic inflammation were increased. For example, amplicon sequence variant (ASV) 362 belonging to the genus Bacteroides and ASV 312 belonging to Tannerellaceae were enriched in no rejection (P < 0.001 and P < 0.01), whereas ASV 365 was enriched in patients with allograft rejection (P = 0.04). Looking at metagenomic functions, a higher abundance of genes coding for enzymes involved in bacterial multidrug resistance and processing of short-chain fatty acids was found in patients without rejection but an increase in enzymes involved in nicotinamide adenine dinucleotide phosphate production was seen in patients with allograft rejection. Conclusions. A distinct microbial fingerprint of patients with allograft rejection might serve as noninvasive biomarker in the future.
CRIS-Team Scopus Importer:2025-02-04

Drugs targeting dynamin can restore cytoskeleton and focal contact alterations of urinary podocytes derived from patients with nephrotic syndrome - Müller-Deile, Janina; Teng, Beina; Schenk, Heiko; Haller, Hermann; Reiser, Jochen; Sever, Sanja; Schiffer, Mario (Annals of Translational Medicine, 2016)
EVALuna2:34573

Fine particulate matter (PM2.5) induces microRNA-192–5p causing glomerular damage - Yarbakht, Melina; Sarau, George; Xu, Yanyi; Fang, Xinyi; Mirzaei, Zeynab; Krüger, René; Xiao, Yalan; Usman, Arslan; Daniel, Christoph; Schiffer, Mario; Christiansen, Silke; Müller-Deile, Janina (Ecotoxicology and Environmental Safety, 2025)
An association between air pollution and the incidence of membranous glomerulonephritis (MGN) has been shown in epidemiological studies. However, the causality of this relationship and data on potential pathomechanisms are still missing. Anti-phospholipase A2 receptor (PLA2R1) antibodies, upregulation of microRNA-192–5p, and decreased expression of its podocyte target nephronectin (NPNT) in patients with MGN have been shown, but the trigger for these regulations remained unknown. The current study aimed to assay the possible role of PM2.5 in the pathogenesis of MGN. In this study, we characterized particulate matter (PM2.5) collected on air filters in Shanghai by scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray fluorescence, microwave plasma atomic emission spectroscopy, nanoparticle tracking analysis, and Raman spectroscopy. Cultured human podocytes, zebrafish, and mice were exposed to PM2.5 to assess possible effects on glomerular function and ultrastructure. PM2.5 caused a reduction of podocyte-specific markers and upregulation of microRNA-192–5p. Moreover, NPNT/npnt/Npnt were downregulated, while PLA2R1/pla2r1/Pla2r1 were upregulated. PM2.5 was able to cause edema, proteinuria, and glomerular damage with loosening of the glomerular basement membrane and partial podocyte effacement in zebrafish larvae. BulkRNA seq analysis and qPCR of zebrafish larvae showed an increase in inflammatory response and oxidative stress due to the exposure to PM2.5. Long-term exposure of mice to ambient PM2.5 induced glomerular damage, albuminuria, and upregulation of pulmonary microRNA-192–5p. Therefore, air pollution might be involved in developing MGN through inflammatory pathways and the induction of microRNA-192–5p, which targets gene expression important for glomerular cell function.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Air pollution; glomerulus; membranous glomerulonephritis; PM; podocytes; proteinuria; zebrafish model

GENERATION OF NOVEL 3D CO-CULTURE SYSTEMS TO STUDY PODOCYTOPATHIES EX VIVO IN A PERSONALIZED MANNER - Rose, Victoria; Sopel, Nina; Ohs, Alexandra; Warnecke, Christina; Schiffer, Mario; Müller-Deile, Janina (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2021)
CRIS-Team WoS Importer:2021-12-03

Generation of Patient-Derived Podocytes from Skin Biopsies - Rose, Victoria; Müller-Deile, Janina (Journal of Visualized Experiments, 2023)
Podocytes are epithelial cells sitting on the urinary site of the glomerular filtration barrier that contribute to the selective filter function of the glomerulus. Mutations in podocyte-specific genes can cause focal segmental glomerulosclerosis (FSGS), and podocytes are also affected in many other primary and secondary nephropathies. Due to their differentiated nature, primary cell culture models are limited for podocytes. Therefore, commonly conditionally immortalized cells are used. However, these conditionally immortalized podocytes (ciPodocytes) have several limitations: the cells can dedifferentiate in culture, especially when they reach confluency, and several podocyte-specific markers are either only slightly or not expressed at all. This brings the use of ciPodocytes and their applicability for physiological, pathophysiological, and clinical reach into question. Here, we describe a protocol for the generation of human podocytes-including patient-specific podocytes-from a skin punch biopsy by episomal reprogramming of dermal fibroblasts into hiPSCs and subsequent differentiation into podocytes. These podocytes resemble in vivo podocytes much better in terms of morphological characteristics, like the development of foot processes and the expression of the podocyte-specific marker. Finally, yet importantly, these cells maintain patients' mutations, resulting in an improved ex vivo model to study podocyte diseases and potential therapeutic substances in an individualized approach.
CRIS-Team Scopus Importer:2023-06-30

GENERATION OF PATIENT-SPECIFIC HIPSC-PODOCYTES TO STUDY PHENOTYPE-SPECIFIC ALTERATIONS AND TEST THERAPEUTIC TARGETS EX VIVO - Rose, Victoria; Sopel, Nina; Ohs, Alexandra; Warnecke, Christina; Schiffer, Mario; Müller-Deile, Janina (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2022)
CRIS-Team WoS Importer:2022-07-22

Glomerular Endothelial Cell-Derived microRNA-192 Regulates Nephronectin Expression in Idiopathic Membranous Glomerulonephritis. - Müller-Deile, Janina; Sopel, Nina; Ohs, Alexandra; Rose, Victoria; Gröner, Marwin; Wrede, Christoph; Hegermann, Jan; Daniel, Christoph; Amann, Kerstin Ute; Zahner, Gunther; Schiffer, Mario (Journal of the American Society of Nephrology, 2021)
BACKGROUND: Autoantibodies binding to podocyte antigens cause idiopathic membranous glomerulonephritis (iMGN). However, it remains elusive how autoantibodies reach the subepithelial space because the glomerular filtration barrier (GFB) is size selective and almost impermeable for antibodies. METHODS: Kidney biopsies from patients with iMGN, cell culture, zebrafish, and mouse models were used to investigate the role of nephronectin (NPNT) regulating microRNAs (miRs) for the GFB. RESULTS: Glomerular endothelial cell (GEC)-derived miR-192-5p and podocyte-derived miR-378a-3p are upregulated in urine and glomeruli of patients with iMGN, whereas glomerular NPNT is reduced. Overexpression of miR-192-5p and morpholino-mediated npnt knockdown induced edema, proteinuria, and podocyte effacement similar to podocyte-derived miR-378a-3p in zebrafish. Structural changes of the glomerular basement membrane (GBM) with increased lucidity, splitting, and lamellation, especially of the lamina rara interna, similar to ultrastructural findings seen in advanced stages of iMGN, were found. IgG-size nanoparticles accumulated in lucidity areas of the lamina rara interna and lamina densa of the GBM in npnt-knockdown zebrafish models. Loss of slit diaphragm proteins and severe structural impairment of the GBM were further confirmed in podocyte-specific Npnt knockout mice. GECs downregulate podocyte NPNT by transfer of miR-192-5p-containing exosomes in a paracrine manner. CONCLUSIONS: Podocyte NPNT is important for proper glomerular filter function and GBM structure and is regulated by GEC-derived miR-192-5p and podocyte-derived miR-378a-3p. We hypothesize that loss of NPNT in the GBM is an important part of the initial pathophysiology of iMGN and enables autoantigenicity of podocyte antigens and subepithelial immune complex deposition in iMGN.
EVALuna2:483425

Glomerular Endothelial Cell-Derived miR-200c Impairs Glomerular Homeostasis by Targeting Podocyte VEGF-A - Ursu, Raluca; Sopel, Nina; Ohs, Alexandra; Tati, Ramesh; Buvall, Lisa; Nyström, Jenny; Schiffer, Mario; Müller-Deile, Janina (International Journal of Molecular Sciences, 2022)
Deciphering the pathophysiological mechanisms of primary podocytopathies that can lead to end-stage renal disease and increased mortality is an unmet need. Studying how microRNAs (miRs) interfere with various signaling pathways enables identification of pathomechanisms, novel biomarkers and potential therapeutic options. We investigated the expression of miR-200c in urine from patients with different renal diseases as a potential candidate involved in podocytopathies. The role of miR-200c for the glomerulus and its potential targets were studied in cultured human podocytes, human glomerular endothelial cells and in the zebrafish model. miR-200c was upregulated in urine from patients with minimal change disease, membranous glomerulonephritis and focal segmental glomerulosclerosis and also in transforming growth factor beta (TGF-β) stressed glomerular endothelial cells, but not in podocytes. In zebrafish, miR-200c overexpression caused proteinuria, edema, podocyte foot process effacement and glomerular endotheliosis. Although zinc finger E-Box binding homeobox 1/2 (ZEB1/2), important in epithelial to mesenchymal transition (EMT), are prominent targets of miR-200c, their downregulation did not explain our zebrafish phenotype. We detected decreased vegfaa/bb in zebrafish overexpressing miR-200c and could further prove that miR-200c decreased VEGF-A expression and secretion in cultured human podocytes. We hypothesize that miR-200c is released from glomerular endothelial cells during cell stress and acts in a paracrine, autocrine, as well as context-dependent manner in the glomerulus. MiR-200c can cause glomerular damage most likely due to the reduction of podocyte VEGF-A. In contrast, miR-200c might also influence ZEB expression and therefore EMT, which might be important in other conditions. Therefore, we propose that miR-200c-mediated effects in the glomerulus are context-sensitive.
CRIS-Team Scopus Importer:2022-12-23
Keywords: endotheliosis; glomerulus; miR-200c; podocytopathies; proteinuria; VEGF-A; zebrafish

Graft Growth and Podocyte Dedifferentiation in Donor-Recipient Size Mismatch Kidney Transplants - Müller-Deile, Janina; Braesen, Jan Hinrich; Pollheimer, Marion; Ratschek, Manfred; Haller, Hermann; Pape, Lars; Schiffer, Mario (Transplantation Direct, 2017)
BACKGROUND: Kidney transplantation is the treatment choice for patients with end-stage renal diseases. Because of good long-term outcome, pediatric kidney grafts are also accepted for transplantation in adult recipients despite a significant mismatch in body size and age between donor and recipient. These grafts show a remarkable ability of adaptation to the recipient body and increase in size in a very short period, presumably as an adaptation to hyperfiltration. METHODS: We investigated renal graft growth as well as glomerular proliferation and differentiation markers Kiel-67, paired box gene 2 and Wilms tumor protein (WT1) expression in control biopsies from different transplant constellations: infant donor for infant recipient, infant donor for child recipient, infant donor for adult recipient, child donor for child recipient, child donor for adult recipient, and adult donor for an adult recipient. RESULTS: We detected a significant increase in kidney graft size after transplantation in all conditions with a body size mismatch, which was most prominent when an infant donated for a child. Podocyte WT1 expression was comparable in different transplant conditions, whereas a significant increase in WT1 expression could be detected in parietal epithelial cells, when a kidney graft from a child was transplanted into an adult. In kidney grafts that were relatively small for the recipients, we could detect reexpression of podocyte paired box gene 2. Moreover, the proliferation marker Kiel-67 was expressed in glomerular cells in grafts that increased in size after transplantation. CONCLUSIONS: Kidney grafts rapidly adapt to the recipient size after transplantation if they are transplanted in a body size mismatch constellation. The increase in transplant size is accompanied by an upregulation of proliferation and dedifferentiation markers in podocytes. The different examined conditions exclude hormonal factors as the key trigger for this growth so that most likely hyperfiltration is the key trigger inducing the rapid growth response.
EVALuna2:34571

HDL in CKD: Not protective any longer - Müller-Deile, Janina; Schmitt, Roland (Kidney International, 2014)
CRIS-Team Scopus Importer:2020-11-12

Loss of the collagen IV modifier prolyl 3-hydroxylase 2 causes thin basement membrane nephropathy - Aypek, Hande; Krisp, Christoph; Lu, Shun; Liu, Shuya; Kylies, Dominik; Kretz, Oliver; Wu, Guochao; Moritz, Manuela; Amann, Kerstin Ute; Benz, Kerstin; Tong, Ping; Hu, Zheng Mao; et al. (Journal of Clinical Investigation, 2022)
The glomerular filtration barrier (GFB) produces primary urine and is composed of a fenestrated endothelium, a glomerular basement membrane (GBM), podocytes, and a slit diaphragm. Impairment of the GFB leads to albuminuria and microhematuria. The GBM is generated via secreted proteins from both endothelial cells and podocytes and is supposed to majorly contribute to filtration selectivity. While genetic mutations or variations of GBM components have been recently proposed to be a common cause of glomerular diseases, pathways modifying and stabilizing the GBM remain incompletely understood. Here, we identified prolyl 3-hydroxylase 2 (P3H2) as a regulator of the GBM in an a cohort of patients with albuminuria. P3H2 hydroxylates the 3′ of prolines in collagen IV subchains in the endoplasmic reticulum. Characterization of a P3h2ΔPod mouse line revealed that the absence of P3H2 protein in podocytes induced a thin basement membrane nephropathy (TBMN) phenotype with a thinner GBM than that in WT mice and the development of microhematuria and microalbuminuria over time. Mechanistically, differential quantitative proteomics of the GBM identified a significant decrease in the abundance of collagen IV subchains and their interaction partners in P3h2ΔPod mice. To our knowledge, P3H2 protein is the first identified GBM modifier, and loss or mutation of P3H2 causes TBMN and focal segmental glomerulosclerosis in mice and humans.
CRIS-Team Scopus Importer:2022-05-20

Moving beyond GWAS and eQTL Analysis to Validated Hits in Chronic Kidney Disease - Müller-Deile, Janina; Jobst-Schwan, Tilman; Schiffer, Mario (Cell Metabolism, 2019)
Genome-wide association studies (GWAS) have identified multiple chronic kidney disease (CKD)-associated single-nucleotide polymorphisms (SNPs) mainly localized to non-coding genomic regions. To understand which genes and which cell types are affected by these genetic variants, compartment-specific transcriptome, genome, and epigenome data were analyzed in an integrative manner in a recent study by Qiu et al. (Qiu et al., 2018).
EVALuna2:118628

Multiplex gene analysis reveals T-cell and antibody-mediated rejection-specific upregulation of complement in renal transplants - Vonbrunn, Eva; Ries, Tajana; Söllner, Stefan; Müller-Deile, Janina; Büttner, Maike; Amann, Kerstin Ute; Daniel, Christoph (Scientific Reports, 2021)
In renal transplantation, complement is involved in ischemia reperfusion injury, graft rejection and dysfunction. However, it is still unclear how induction of complement and its activation are initiated. Using allograft biopsies of a well-characterized cohort of 28 renal transplant patients with no rejection (Ctrl), delayed graft function (DGF), acute T-cell-mediated (TCMR) or antibody-mediated rejection (ABMR) we analyzed differences in complement reaction. For that mRNA was isolated from FFPE sections, quantified with a multiplex gene expression panel and correlated with transplant conditions and follow-up of patients. Additionally, inflammatory cells were quantified by multiplex immunohistochemistry. In allograft biopsies with TCMR and ABMR gene expression of C1QB was 2-4 fold elevated compared to Ctrl. In TCMR biopsies, mRNA counts of several complement-related genes including C1S, C3, CFB and complement regulators CFH, CR1 and SERPING1 were significantly increased compared to Ctrl. Interestingly, expression levels of about 75% of the analyzed complement related genes correlated with cold ischemia time (CIT) and markers of inflammation. In conclusion, this study suggest an important role of complement in transplant pathology which seems to be at least in part triggered by CIT. Multiplex mRNA analysis might be a useful method to refine diagnosis and explore new pathways involved in rejection.
CRIS-Team Scopus Importer:2021-08-13

Mutation of microphthalmia-associated transcription factor (mitf) in zebrafish sensitizes for glomerulopathy - Müller-Deile, Janina; Schenk, Heiko; Niggemann, Philipp; Bolanõs-Palmieri, Patricia; Teng, Beina; Higgs, Alysha; Staggs, Lynne; Haller, Hermann; Schroder, Patricia; Schiffer, Mario (Biology Open, 2019)
Different glomerular diseases that affect podocyte homeostasis can clinically present as nephrotic syndrome with massive proteinuria, hypoalbuminemia, hyperlipidemia and edema. Up to now, no drugs that specifically target the actin cytoskeleton of podocytes are on the market and model systems for library screenings to develop anti-proteinuric drugs are of high interest. We developed a standardized proteinuria model in zebrafish using puromycin aminonucleoside (PAN) via treatment in the fish water to allow for further drug testing to develop anti-proteinuric drugs for the treatment of glomerular diseases. We noticed that fish that carry the nacre-mutation show a significantly higher susceptibility for the disruption of the glomerular filtration barrier following PAN treatment, which results in a more pronounced proteinuria phenotype. Nacre zebrafish inherit a mutation yielding a truncated version of microphthalmia-associated transcription factor/melanogenesis associated transcription factor (mitf). We hypothesized that the nacre mutation may lead to reduced formin expression and defects in cytoskeletal rearrangement. Based on the observations in zebrafish, we carried out a PAN treatment on cultured human podocytes after knockdown with MITF siRNA causing a rearrangement of the actin cytoskeleton.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Glomerulopathy; MITF; PAN; Podocyte; Zebrafish

Novel diagnostic and therapeutic techniques reveal changed metabolic profiles in recurrent focal segmental glomerulosclerosis - Müller-Deile, Janina; Sarau, George; Kotb, Ahmed M.; Jaremenko, Christian; Rolle-Kampczyk, Ulrike E.; Daniel, Christoph; Kalkhof, Stefan; Christiansen, Silke H.; Schiffer, Mario (Scientific Reports, 2021)
Idiopathic forms of Focal Segmental Glomerulosclerosis (FSGS) are caused by circulating permeability factors, which can lead to early recurrence of FSGS and kidney failure after kidney transplantation. In the past three decades, many research endeavors were undertaken to identify these unknown factors. Even though some potential candidates have been recently discussed in the literature, “the” actual factor remains elusive. Therefore, there is an increased demand in FSGS research for the use of novel technologies that allow us to study FSGS from a yet unexplored angle. Here, we report the successful treatment of recurrent FSGS in a patient after living-related kidney transplantation by removal of circulating factors with CytoSorb apheresis. Interestingly, the classical published circulating factors were all in normal range in this patient but early disease recurrence in the transplant kidney and immediate response to CytoSorb apheresis were still suggestive for pathogenic circulating factors. To proof the functional effects of the patient’s serum on podocytes and the glomerular filtration barrier we used a podocyte cell culture model and a proteinuria model in zebrafish to detect pathogenic effects on the podocytes actin cytoskeleton inducing a functional phenotype and podocyte effacement. We then performed Raman spectroscopy in the < 50 kDa serum fraction, on cultured podocytes treated with the FSGS serum and in kidney biopsies of the same patient at the time of transplantation and at the time of disease recurrence. The analysis revealed changes in podocyte metabolome induced by the FSGS serum as well as in focal glomerular and parietal epithelial cell regions in the FSGS biopsy. Several altered Raman spectra were identified in the fractionated serum and metabolome analysis by mass spectrometry detected lipid profiles in the FSGS serum, which were supported by disturbances in the Raman spectra. Our novel innovative analysis reveals changed lipid metabolome profiles associated with idiopathic FSGS that might reflect a new subtype of the disease.
CRIS-Team Scopus Importer:2021-03-19

NOVEL DIAGNOSTIC AND THERAPEUTIC TECHNIQUES REVEAL CHANGED METABOLOMIC PROFILE IN RECURRENT FOCAL SEGMENTAL GLOMERULOSCLEROSIS - Müller-Deile, Janina; Sarau, George; Kotb, Ahmed; Daniel, Christoph; Kalkhof, Stefan; Christiansen, Silke; Schiffer, Mario (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2021)
CRIS-Team WoS Importer:2021-12-03
Keywords: Transplantation; Urology & Nephrology

Online Kt/V monitoring in haemodialysis by UV absorbance: Variations during intra-dialytic meals - Müller-Deile, Janina; Lichtinghagen, Ralf; Haller, Hermann; Schmitt, Roland (Blood Purification, 2014)
Background/Aims: The aim of this study was to analyse if intra-dialytic food intake may lead to changes in online Kt/V. Methods: Forty patients were analysed using haemodialysis machines with integrated online Kt/V monitoring based on UV absorbance or ionic dialysance. Kt/V was monitored before, during and after food intake. Samples of dialysate were analysed for urea, uric acid, creatinine and glucose levels. Results: Food intake was associated with a significant decrease in relative Kt/V when determined by UV absorbance. The drop in Kt/V was independent of changes in blood pressure or body posture. No significant changes in online Kt/V were found using the ionic dialysance method. Dialysate samples showed a continuous clearance of urea, uric acid and creatinine during meals but a rapid increase in glucose. Conclusion: Our data suggest that the short meal-associated decrease in online Kt/V as measured by UV absorbance does not represent a true decline in Kt/V but might reflect an intermittent increase in UV-absorbing dialysed solutes. © 2014 S. Karger AG, Basel.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Haemodialysis; Intra-dialytic meals; Kt/V; UV absorbance

Overexpression of preeclampsia induced microRNA-26a-5p leads to proteinuria in zebrafish - Müller-Deile, Janina; Schroeder, Patricia; Beverly-Staggs, Lynne; Hiss, Rebecca; Fiedler, Jan; Nystroem, Jenny; Thum, Thomas; Haller, Hermann; Schiffer, Mario (Scientific Reports, 2018)
So far the pathomechanism of preeclampsia in pregnancy is focussed on increased circulating levels of soluble fms-like tyrosin kinase-1 (sFLT-1) that neutralizes glomerular VEGF-A expression and prevents its signaling at the glomerular endothelium. As a result of changed glomerular VEGF-A levels endotheliosis and podocyte foot process effacement are typical morphological features of preeclampsia. Recently, microRNA-26a-5p (miR-26a-5p) was described to be also upregulated in the preeclamptic placenta. We found that miR-26a-5p targets VEGF-A expression by means of PIK3C2α in cultured human podocytes and that miR-26a-5p overexpression in zebrafish causes proteinuria, edema, glomerular endotheliosis and podocyte foot process effacement. Interestingly, recombinant zebrafish Vegf-Aa protein could rescue glomerular changes induced by miR-26a-5p. In a small pilot study, preeclamptic patients with podocyte damage identified by podocyturia, expressed significantly more urinary miR-26a-5p compared to healthy controls. Thus, functional and ultrastructural glomerular changes after miR-26a-5p overexpression can resemble the findings seen in preeclampsia and indicate a potential pathophysiological role of miR-26a-5p in addition to sFLT-1 in this disease.
EVALuna2:34543

Overexpression of TGF-β Inducible microRNA-143 in Zebrafish Leads to Impairment of the Glomerular Filtration Barrier by Targeting Proteoglycans - Müller-Deile, Janina; Gellrich, Finn; Schenk, Heiko; Schroder, Patricia; Nystrom, Jenny; Lorenzen, Johan; Haller, Hermann; Schiffer, Mario (Cellular Physiology and Biochemistry, 2016)
BACKGROUND: TGF-β is known as an important stress factor of podocytes in glomerular diseases. Apart from activation of direct pro-apoptotic pathways we wanted to analyze micro-RNA (miRs) driven regulation of components involved in the integrity of the glomerular filtration barrier induced by TGF-β. Since miR-143-3p (miR-143) is described as a TGF-β inducible miR in other cell types, we examined this specific miR and its ability to induce glomerular pathology. METHODS: We analyzed miR-143 expression in cultured human podocytes after stimulation with TGF-β. We also microinjected zebrafish eggs with a miR-143 mimic or with morpholinos specific for its targets syndecan and versican and compared phenotype and proteinuria development. RESULTS: We detected a time dependent, TGF-β inducible expression of miR-143 in human podocytes. Targets of miR-143 relevant in glomerular biology are syndecans and versican, which are known components of the glycocalyx. We found that syndecan 1 and 4 were predominantly expressed in podocytes while syndecan 3 was largely expressed in glomerular endothelial cells. Versican could be detected in both cell types. After injection of a miR-143 mimic in zebrafish larvae, syndecan 3, 4 and versican were significantly downregulated. Moreover, miR-143 overexpression or versican knockdown by morpholino caused loss of plasma proteins, edema, podocyte effacement and endothelial damage. In contrast, knockdown of syndecan 3 and syndecan 4 had no effects on glomerular filtration barrier. CONCLUSION: Expression of versican and syndecan isoforms is indispensable for proper barrier function. Podocyte-derived miR-143 is a mediator for paracrine and autocrine cross talk between podocytes and glomerular endothelial cells and can alter expression of glomerular glycocalyx proteins.
EVALuna2:34558

Oxysterol-binding protein-like 7 deficiency leads to ER stress-mediated apoptosis in podocytes and proteinuria - Duara, Joanne; Torres, Maria; Gurumani, Margaret; David, Judith Molina; Njeim, Rachel; Kim, Jin Ju; Mitrofanova, Alla; Ge, Mengyuan; Sloan, Alexis; Müller-Deile, Janina; Schiffer, Mario; Merscher, Sandra; et al. (American Journal of Physiology-Renal Physiology, 2024)
Chronic kidney disease (CKD) is associated with renal lipid dysmetabolism among a variety of other pathways. We recently demonstrated that oxysterol-binding protein-like 7 (OSBPL7) modulates the expression and function of ATP-binding cassette subfamily A member 1 (ABCA1) in podocytes, a specialized type of cell essential for kidney filtration. Drugs that target OSBPL7 lead to improved renal outcomes in several experimental models of CKD. However, the role of OSBPL7 in podocyte injury remains unclear. Using mouse models and cellular assays, we investigated the influence of OSBPL7 deficiency on podocytes. We demonstrated that reduced renal OSBPL7 levels as observed in two different models of experimental CKD are linked to increased podocyte apoptosis, primarily mediated by heightened endoplasmic reticulum (ER) stress. Although as expected, the absence of OSBPL7 also resulted in lipid dysregulation (increased lipid droplets and triglycerides content), OSBPL7 deficiency-related lipid dysmetabolism did not contribute to podocyte injury. Similarly, we demonstrated that the decreased autophagic flux we observed in OSBPL7-deficient podocytes was not the mechanistic link between OSBPL7 deficiency and apoptosis. In a complementary zebrafish model, osbpl7 knockdown was sufficient to induce proteinuria and morphological damage to the glomerulus, underscoring its physiological relevance. Our study sheds new light on the mechanistic link between OSBPL7 deficiency and podocyte injury in glomerular diseases associated with CKD, and it strengthens the role of OSBPL7 as a novel therapeutic target.
CRIS-Team Scopus Importer:2024-08-30
Keywords: chronic kidney disease; ER stress; glomerular disease; podocytes; proteinuria

Partner, Neighbor, Housekeeper and Dimension: 3D versus 2D Glomerular Co-Cultures Reveal Drawbacks of Currently Used Cell Culture Models - Rederer, Anna; Rose, Victoria; Krüger, René; Schmittutz, Linda; Swierzy, Izabela; Fischer, Lena; Thievessen, Ingo; Bauer, Julian; Friedrich, Oliver; Schiffer, Mario; Müller-Deile, Janina (International Journal of Molecular Sciences, 2023)
Signaling-pathway analyses and the investigation of gene responses to different stimuli are usually performed in 2D monocultures. However, within the glomerulus, cells grow in 3D and are involved in direct and paracrine interactions with different glomerular cell types. Thus, the results from 2D monoculture experiments must be taken with caution. We cultured glomerular endothelial cells, podocytes and mesangial cells in 2D/3D monocultures and 2D/3D co-cultures and analyzed cell survival, self-assembly, gene expression, cell–cell interaction, and gene pathways using live/dead assay, time-lapse analysis, bulk-RNA sequencing, qPCR, and immunofluorescence staining. Without any need for scaffolds, 3D glomerular co-cultures self-organized into spheroids. Podocyte- and glomerular endothelial cell-specific markers and the extracellular matrix were increased in 3D co-cultures compared to 2D co-cultures. Housekeeping genes must be chosen wisely, as many genes used for the normalization of gene expression were themselves affected in 3D culture conditions. The transport of podocyte-derived VEGFA to glomerular endothelial cells confirmed intercellular crosstalk in the 3D co-culture models. The enhanced expression of genes important for glomerular function in 3D, compared to 2D, questions the reliability of currently used 2D monocultures. Hence, glomerular 3D co-cultures might be more suitable in the study of intercellular communication, disease modelling and drug screening ex vivo.
Created from Fastlane, Scopus look-up
Keywords: 3D co-culture; bulk-RNA sequencing; cell culture model; cell matrix; cell–cell communication; glomerular spheroids

PODOCYTE AND GLOMERULAR ENDOTHELIAL CELL DERIVED MICRORNAS REGULATE PODOCYTE NEPHRONECTIN IN MEMBRANOUS GLOMERULONEPHRITIS - Müller-Deile, Janina; Sopel, Nina; Ohs, Alexandra; Kotb, Ahmed; Gröner, Marwin; Daniel, Christoph; Amann, Kerstin Ute; Schiffer, Mario (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2021)
CRIS-Team WoS Importer:2021-12-03

Podocyte directed therapy of nephrotic syndrome-can we bring the inside out? - Müller-Deile, Janina; Schiffer, Mario (Pediatric Nephrology, 2016)
Several of the drugs currently used for the treatment of glomerular diseases are prescribed for their immunotherapeutic or anti-inflammatory properties, based on the current understanding that glomerular diseases are mediated by immune responses. In recent years our understanding of podocytic signalling pathways and the crucial role of genetic predispositions in the pathology of glomerular diseases has broadened. Delineation of those signalling pathways supports the hypothesis that several of the medications and immunosuppressive agents used to treat glomerular diseases directly target glomerular podocytes. Several central downstream signalling pathways merge into regulatory pathways of the podocytic actin cytoskeleton and its connection to the slit diaphragm. The slit diaphragm and the cytoskeleton of the foot process represent a functional unit. A breakdown of the cytoskeletal backbone of the foot processes leads to internalization of slit diaphragm molecules, and internalization of slit diaphragm components in turn negatively affects cytoskeletal signalling pathways. Podocytes display a remarkable ability to recover from complete effacement and to re-form interdigitating foot processes and intact slit diaphragms after pharmacological intervention. This ability indicates an active inside-out signalling machinery which stabilizes integrin complex formations and triggers the recycling of slit diaphragm molecules from intracellular compartments to the cell surface. In this review we summarize current evidence from patient studies and model organisms on the direct impact of immunosuppressive and supportive drugs on podocyte signalling pathways. We highlight new therapeutic targets that may open novel opportunities to enhance and stabilize inside-out pathways in podocytes.
EVALuna2:34557

PODOCYTE NEPHRONECTIN IS REGULATED BY TRANSFORMING GROWTH FACTOR BETA VIA THE CANONICAL AND NON-CANONICAL PATHWAYS - Sopel, Nina; Ohs, Alexandra; Schiffer, Mario; Müller-Deile, Janina (NEPHROLOGY DIALYSIS TRANSPLANTATION, 2021)
CRIS-Team WoS Importer:2021-12-03

Podocytes from the diagnostic and therapeutic point of view - Müller-Deile, Janina; Schiffer, Mario (Pflügers Archiv: European Journal of Physiology, 2017)
The central role of podocytes in glomerular diseases makes this cell type an interesting diagnostic tool as well as a therapeutic target. In this review, we discuss the current literature on the use of podocytes and podocyte-specific markers as non-invasive diagnostic tools in different glomerulopathies. Furthermore, we highlight the direct effects of drugs currently used to treat primary glomerular diseases and describe their direct cellular effects on podocytes. A new therapeutic potential is seen in drugs targeting the podocytic actin cytoskeleton which is essential for podocyte foot process structure and function. Incubation of cultured human podocyte cell lines with sera from patients with active glomerular diseases is currently also used to identify novel circulating factors with pathophysiological relevance for the glomerular filtration barrier. In addition, treatment of detached urinary podocytes from patients with substances that restore their cytoskeleton might serve as a novel personalized tool to estimate their potential for podocyte recovery ex vivo.
EVALuna2:34549

Podocytes regulate the glomerular basement membrane protein nephronectin by means of miR-378a-3p in glomerular diseases - Müller-Deile, Janina; Dannenberg, Jan; Schroder, Patricia; Lin, Meei-Hua; Miner, Jeffrey H.; Chen, Rongjun; Braesen, Jan-Hinrich; Thum, Thomas; Nystrom, Jenny; Staggs, Lynne Beverly; Haller, Hermann; Fiedler, Jan; et al. (Kidney International, 2017)
The pathophysiology of many proteinuric kidney diseases is poorly understood, and microRNAs (miRs) regulation of these diseases has been largely unexplored. Here, we tested whether miR-378a-3p is a novel regulator of glomerular diseases. MiR-378a-3p has two predicted targets relevant to glomerular function, the glomerular basement membrane matrix component, nephronectin (NPNT), and vascular endothelial growth factor VEGF-A. In zebrafish (Danio rerio), miR-378a-3p mimic injection or npnt knockdown by a morpholino oligomer caused an identical phenotype consisting of edema, proteinuria, podocyte effacement, and widening of the glomerular basement membrane in the lamina rara interna. Zebrafish vegf-A protein could not rescue this phenotype. However, mouse Npnt constructs containing a mutated 3'UTR region prevented the phenotype caused by miR-378a-3p mimic injection. Overexpression of miR-378a-3p in mice confirmed glomerular dysfunction in a mammalian model. Biopsies from patients with focal segmental glomerulosclerosis and membranous nephropathy had increased miR-378a-3p expression and reduced glomerular levels of NPNT. Thus, miR-378a-3p-mediated suppression of the glomerular matrix protein NPNT is a novel mechanism for proteinuria development in active glomerular diseases.
EVALuna2:34547

Removal of focal segmental glomerulosclerosis (FSGS) factor suPAR using CytoSorb - Schenk, Heiko; Müller-Deile, Janina; Schmitt, Roland; Braesen, Jan Hinrich; Haller, Hermann; Schiffer, Mario (Journal of Clinical Apheresis, 2017)
Treatment of primary focal segmental glomerulosclerosis (FSGS) and its recurrence after kidney transplantation associated with rapid deterioration of kidney function remains to be challenging despite advances in immunosuppressive therapy. The presence of circulating factors has been postulated to be a pivotal player in the pathogenesis of FSGS, although suPAR and CLCF-1 have been identified as the most promising causative factors. The potential therapeutic effect of suPAR elimination in an FSGS patient using CytoSorb, a hemoadsorption device that gained attention in the cytokine elimination in septic patients, was studied. Efficiency of total plasma exchange to remove suPAR was determined. CytoSorb hemoadsorption caused a 27.33% reduction of the suPAR level in a single treatment, whereas total plasma exchange showed a suPAR level reduction of 25.12% (n = 3; 95% confidence interval, 0.2777-0.8090; P < 0.01), which may indicate therapeutic potential in the treatment of primary FSGS and its recurrence in a kidney transplant.
EVALuna2:34545

Renal involvement in preeclampsia: similarities to VEGF ablation therapy. - Müller-Deile, Janina; Schiffer, Mario (Journal of Pregnancy, 2011)
Glomerular VEGF expression is critical for the maintenance and function of an intact filtration barrier. Alterations in glomerular VEGF bioavailability result in endothelial as well as in podocyte damage. Renal involvement in preeclampsia includes proteinuria, podocyturia, elevated blood pressure, edema, glomerular capillary endotheliosis, and thrombotic microangiopathy. At least the renal signs, symptoms, and other evidence can sufficiently be explained by reduced VEGF levels. The aim of this paper was to summarize our pathophysiological understanding of the renal involvement of preeclampsia and point out similarities to the renal side effects of VEGF-ablation therapy.
CRIS-Team Scopus Importer:2020-11-12

Renal side effects of VEGF-blocking therapy - Müller-Deile, Janina; Broecker, Verena; Grünwald, Viktor; Hiss, Marcus; Bertram, Anna; Kubicka, Stefan; Ganser, Arnold; Haller, Hermann; Schiffer, Mario (NDT Plus, 2010)
CRIS-Team Scopus Importer:2020-11-12
Keywords: bevacizumab; podocyturia; sunitinib; VEGF

Role of endothelial microRNA 155 on capillary leakage in systemic inflammation - Etzrodt, Valerie; Idowu, Temitayo O.; Schenk, Heiko; Seeliger, Benjamin; Prasse, Antje; Thamm, Kristina; Pape, Thorben; Müller-Deile, Janina; van Meurs, Matijs; Thum, Thomas; Garg, Ankita; Geffers, Robert; et al. (Critical Care, 2021)
Background: Capillary leakage is a key contributor to the pathological host response to infections. The underlying mechanisms remain incompletely understood, and the role of microRNAs (MIR) has not been investigated in detail. We hypothesized that specific MIRs might be regulated directly in the endothelium thereby contributing to vascular leakage. Methods: SmallRNA sequencing of endotoxemic murine pulmonary endothelial cells (ECs) was done to detect regulated vascular MIRs. In vivo models: transgenic zebrafish (flk1:mCherry/l-fabp:eGFP-DPB), knockout/wildtype mouse (B6.Cg-Mir155tm1.1Rsky/J); disease models: LPS 17.5 mg/kgBW and cecal ligation and puncture (CLP); in vitro models: stimulated human umbilical vein EC (HUVECs), transendothelial electrical resistance. Results: Endothelial MIR155 was identified as a promising candidate in endotoxemic murine pulmonary ECs (25 × upregulation). Experimental overexpression in a transgenic zebrafish line and in HUVECs was sufficient to induce spontaneous vascular leakage. To the contrary, genetic MIR155 reduction protects against permeability both in vitro and in endotoxemia in vivo in MIR155 heterozygote knockout mice thereby improving survival by 40%. A tight junction protein, Claudin-1, was down-regulated both in endotoxemia and by experimental MIR155 overexpression. Translationally, MIR155 was detectable at high levels in bronchoalveolar fluid of patients with ARDS compared to healthy human subjects. Conclusions: We found that MIR155 is upregulated in the endothelium in mouse and men as part of a systemic inflammatory response and might contribute to the pathophysiology of vascular leakage in a Claudin-1-dependent manner. Future studies have to clarify whether MIR155 could be a potential therapeutic target. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-03-05
Keywords: Endothelium; MicroRNAs; Respiratory distress syndrome; Sepsis; Tight junctions

The balance of autocrine VEGF-A and VEGF-C determines podocyte survival - Müller-Deile, Janina; Worthmann, Kirstin; Saleem, Moin; Tossidou, Irini; Haller, Hermann; Schiffer, Mario (American Journal of Physiology-Renal Physiology, 2009)
Podocytes are an important component of the glomerular filtration barrier and are the major source of vascular endothelial growth factor (VEGF) in the glomerulus. The role of VEGF for the phenotype of the glomerular endothelium has been intensely studied; however, the direct effects of autocrine VEGF on the podocyte are largely unknown. In this study we characterized the expression of VEGF isoforms and VEGF receptors in cultured human podocytes and examined direct effects on cell signaling and apoptosis after stimulation with exogenous VEGF or ablation of autocrine VEGF. We identified VEGF-A and VEGF-C as the dominant isoforms in human podocytes and showed that autocrine levels of both are important for the intracellular activation of antiapoptotic phosphoinositol 3-kinase/AKT and suppression of the proapoptotic p38MAPK via VEGFR-2. We demonstrated that ablation of VEGF-A or VEGF-C as well as treatment with bevacizumab or a VEGFR-2/-3 tyrosine kinase inhibitor led to reduced podocyte survival. In contrast, ablation of VEGF-B had no effect on podocyte survival. Treatment with exogenous VEGF-C reversed the effect of VEGF-A neutralization, and exogenous VEGF-A abrogated the effect of VEGF-C ablation in human podocytes. Our results underline the importance of autocrine VEGF for podocyte survival and indicate the delicate balance of VEGF-A and VEGF-C to influence progression of glomerular diseases. Copyright © 2009 the American Physiological Society.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Apoptosis; Cell survival

The podocyte power-plant disaster and its contribution to glomerulopathy - Müller-Deile, Janina; Schiffer, Mario (Frontiers in Endocrinology, 2014)
Proper podocyte function within the glomerulus demands a high and continuous energy supply that is mainly derived from the respiratory chain of the inner mitochondrial membrane. Dysregulations in the metabolic homeostasis of podocytes may result in podocyte damage and glomerular disease. This article highlights the current knowledge about podocyte energy supply by the respiratory chain. We review the regulation of mitochondrial oxidative metabolism with regard to podocytopathy and discuss the latest understanding of different mitochondrial dysfunctions of the podocyte in diabetic nephropathy and focal segmental glomerulosclerosis (FSGS). We discuss genetic forms of mitochondriopathy of the podocyte and end with recent knowledge about crosstalk between NADH and NADPH and potential therapeutic options for podocyte mitochondriopathy. We aim to raise awareness for the complex and interesting mechanisms of podocyte damage by impaired energy supply that, despite of novel findings in recent years, is poorly understood so far.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Diabetic nephropathy; Energy supply; FSGS; Mitochondria; Mitochondriopathy; Nox; Podocyte

The zebrafish model to understand epigenetics in renal diseases - Sopel, Nina; Müller-Deile, Janina (International Journal of Molecular Sciences, 2021)
Epigenetic modifications are able to alter gene expression and include DNA methylation, different histone variants, and post-transcriptional modifications (PTMs), such as acetylation or phosphorylation, and through short/long RNAs, respectively. In this review, we focus on current knowledge concerning epigenetic modifications in gene regulation. We describe different forms of epigenetic modifications and explain how epigenetic changes can be detected. The relevance of epigenetics in renal diseases is highlighted with multiple examples and the use of the zebrafish model to study glomerular diseases in general and epigenetics in renal diseases in particular is discussed. We end with an outlook on how to use epigenetic modifications as a therapeutic target for different diseases. Here, the zebrafish model can be employed as a high-throughput screening tool not only to discover epigenetic alterations contributing to disease, but also to test novel substances that change epigenetic signatures in vivo. Therefore, the zebrafish model harbors the opportunity to find novel pathogenic pathways allowing a pre-selection of potential targets and compounds to be tested for renal diseases.
CRIS-Team Scopus Importer:2021-09-03
Keywords: DNA methylation; Epigenetics; Histone modifications; MicroRNAs; Renal diseases; Zebrafish model

Thromboembolie in die Arterie eines Nierentransplantats durch Vorhofflimmern - Müller-Deile, Janina; Schwarz, A.; Menne, J. (Nieren- und Hochdruckkrankheiten, 2014)
Background: Central and peripheral arterial thromboembolisms are well known complications of atrial fibrillation. We report the first case of thromboembolism in a renal transplant due to atrial fibrillation after changing anticoagulation treatment. Case presentation: A 79-year-old woman who had undergone kidney transplantation in 2001 had a stable serum of 130-150 μmol/L since transplantation. Because of atrial fibrillation, the patient received oral anticoagulation treatment with Marcumar for many years until it was switched to aspirin (100 mg/d) due to a cholecystectomy in 2012. Three weeks thereafter is when the patient was admitted to our unit with abdominal pain and oliguria. In a computed tomography scan of the abdomen, multiple renal infarcts were detected. The thromboembolism resulted in a complete loss of transplant function. As the patient remained anuric, the transplant was declared to be lost, immunosuppression was reduced, and renal replacement therapy was commenced over a central catheter. However, the patient died the next day. Conclusion: Our case highlights the fact that changing anticoagulation treatment should be performed carefully and can be detrimental. The location of thromboembolism in renal transplant artery makes this case unique and has not ever been described thus far. As renal transplantation and risk factors for thromboembolism i.e., atrial fibrillation are increasing, embolization in renal transplant artery is a potential reason for abdominal pain and anuria; physicians should take this into consideration when treating transplanted patients. © 2014 Dustri-Verlag Dr. Karl Feistle.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Atrial fibrillation; Kidney transplantation; Thromboembolization

Tyrosine Phosphorylation of CD2AP Affects Stability of the Slit Diaphragm Complex - Tossidou, Irini; Teng, Beina; Worthmann, Kirstin; Müller-Deile, Janina; Jobst-Schwan, Tilman; Kardinal, Christian; Schroder, Patricia; Bolanos-Palmieri, Patricia; Haller, Hermann; Willerding, Jonas; Drost, Dana M.; de Jonge, Laura; et al. (Journal of the American Society of Nephrology, 2019)
BACKGROUND: CD2-associated protein (CD2AP), a slit diaphragm-associated scaffolding protein involved in survival and regulation of the cytoskeleton in podocytes, is considered a "stabilizer" of the slit diaphragm complex that connects the slit diaphragm protein nephrin to the cytoskeleton of the cell. Tyrosine phosphorylation of slit diaphragm molecules can influence their surface expression, but it is unknown whether tyrosine phosphorylation events of CD2AP are also physiologically relevant to slit diaphragm stability. METHODS: We used isoelectric focusing, western blot analysis, and immunofluorescence to investigate phosphorylation of CD2AP, and phospho-CD2AP antibodies and site-directed mutagenesis to define the specific phosphorylated tyrosine residues. We used cross-species rescue experiments in Cd2apKD zebrafish and in Drosophila cindrRNAi mutants to define the physiologic relevance of CD2AP phosphorylation of the tyrosine residues. RESULTS: We found that VEGF-A stimulation can induce a tyrosine phosphorylation response in CD2AP in podocytes, and that these phosphorylation events have an important effect on slit diaphragm protein localization and functionality in vivo. We demonstrated that tyrosine in position Y10 of the SH3-1 domain of CD2AP is indispensable for CD2AP function in vivo. We found that the binding affinity of nephrin to CD2AP is significantly enhanced in the absence of Y10; however, unexpectedly, this increased affinity leads not to stabilization but to functional impairment of the glomerular filtration barrier. CONCLUSIONS: Our findings provide insight into CD2AP and its phosphorylation in the context of slit diaphragm functionality, and indicate a fine-tuned affinity balance of CD2AP and nephrin that is influenced by receptor tyrosine kinase stimulation.
CRIS-Team Scopus Importer:2019-07-26
Keywords: CD2AP; nephrin; Phosphorylation; podocyte

WHEN YOUR PARTNER MAKES YOU SICK. A NEW MODEL TO INDUCE PROTEINURIA IN ZEBRAFISH USING PARABIOSIS - Müller-Deile, Janina; Schenk, Heiko; Schroder, Patricia; Schroder, Patricia; Haller, Hermann; Schiffer, Mario (2018)
EVALuna2:35235

Zebrafish Model to Study Podocyte Function Within the Glomerular Filtration Barrier - Sopel, Nina; Müller-Deile, Janina (Methods in Molecular Biology, 2023)
The zebrafish model has been used in many different fields of research because of its high homology to the human genome, its easy genetic manipulation, its high fecundity, and its rapid development. For glomerular diseases, zebrafish larvae have proven to be a versatile tool to study the contribution of different genes, because the zebrafish pronephros is very comparable to the human kidney in function and ultrastructure. Here we describe the principle and use of a simple screening assay based on the measurement of the fluorescence in the retinal vessel plexus of the Tg(l-fabp:DBP:eGFP) zebrafish line ("eye assay") to indirectly determine proteinuria as a hallmark of podocyte dysfunction. Furthermore, we illustrate how to analyze the obtained data and outline methods to attribute the findings to podocyte impairment.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Fluorescence-based assay; Glomerular disease; Kidney; Podocyte; Proteinuria; Zebrafish; “Eye assay”

Клинические практические рекомендации IPNA по диагностике и лечению детей со стероид-резистентным нефротическим синдромом - Trautmann, Agnes; Vivarelli, Marina; Samuel, Susan; Gipson, Debbie; Sinha, Aditi; Schaefer, Franz; Hui, Ng Kar; Boyer, Olivia; Saleem, Moin A.; Feltran, Luciana; Müller-Deile, Janina; Becker, Jan Ulrich; et al. (Нефрология и диализ, 2021)
Idiopathic nephrotic syndrome newly affects 1-3 per 100,000 children per year. Approximately 85% of cases show complete remission of proteinuria following glucocorticoid treatment. Patients who do not achieve complete remission within 4-6 weeks of glucocorticoid treatment have steroid-resistant nephrotic syndrome (SRNS). In 10-30% of steroid resistant patients, mutations in podocyte-associated genes can be detected, whereas an undefined circulating factor of immune origin is assumed in the remaining ones. Diagnosis and management of SRNS is a great challenge due to its heterogeneous etiology, frequent lack of remission by further immunosuppressive treatment, and severe complications including the development of end-stage kidney disease and recurrence after renal transplantation. A team of experts including pediatric nephrologists and renal geneticists from the International Pediatric Nephrology Association (IPNA), a renal pathologist, and an adult nephrologist have now developed comprehensive clinical practice recommendations on the diagnosis and management of SRNS in children. The team performed a systematic literature review on 9 clinically relevant PICO (Patient or Population covered, Intervention, Comparator, Outcome) questions, formulated recommendations and formally graded them at a consensus meeting, with input from patient representatives and a dietician acting as external advisors and a voting panel of pediatric nephrologists. Research recommendations are also given.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Children; Chronic kidney disease; Genetics; Immunosuppressive treatment; Outcome; Pediatrics; Steroid-resistant nephrotic syndrome